Lactate acquisition promotes successful colonization of the murine genital tract by Neisseria gonorrhoeae. - Exley, R; Wu, H; Shaw, J; Schneider, M; Smith, H; Jerse, A; Tang, C (2007)
Previous studies on Neisseria gonorrhoeae have demonstrated that metabolism of lactate in the presence of glucose increases the growth rate of the bacterium and enhances its resistance to complement-mediated killing. Although these findings in vitro suggest that the acquisition of lactate promotes gonococcal colonization, the significance of this carbon source to the survival of the gonococcus in vivo remains unknown. To investigate the importance of lactate utilization during Neisseria gonorrhoeae genital tract infection, we identified the gene lctP, which encodes the gonococcal lactate permease. A mutant that lacks a functional copy of lctP was unable to take up exogenous lactate and did not grow in defined medium with lactate as the sole carbon source, in contrast to the wild-type and complemented strains; the mutant strain exhibited no growth defect in defined medium containing glucose. In defined medium containing physiological concentrations of lactate and glucose, the lctP mutant demonstrated reduced early growth and increased sensitivity to complement-mediated killing compared with the wild-type strain; the enhanced susceptibility to complement was associated with a reduction in lipopolysaccharide sialylation of the lctP mutant. The importance of lactate utilization during colonization was evaluated in the murine model of lower genital tract infection. The lctP mutant was significantly attenuated in its ability to colonize and survive in the genital tract, while the complemented mutant exhibited no defect for colonization. Lactate is a micronutrient in the genital tract that contributes to the survival of the gonococcus.